Pengaruh Citra Merek, Kualitas Produk, dan Persepsi Harga terhadap Keputusan Pembelian Paket Internet Smartfren Super 4G Unlimited - Bella Yunita; Tandiyo Pradekso (Interaksi Online, 2020)
This study aims to determine whether there is an influence of brand image, product quality, and price perception on purchasing decisions of the Smartfren Super 4G Unlimited internet package. This research is an explanatory research object of men and women aged 17-25 years who know or use the Smartfren Super 4G Unlimited internet package in the city of Semarang. Testing is done using simple linear analysis. The results showed that the three variables did not have an influence on purchasing decisions of the Smartfren Super 4G Unlimited internet package with a significant value of brand image of 0.626 (> 0.05), product quality of 0.708 (> 0.05), and price perception of 0.331 (> 0.05).